Методичні основи побудови системи інтелектуальної підтримки прийняття рішень щодо організації збору та переробки органічної сировини в біогазових комплексах - Шворов, С. А.; Комарчук, Д. С.; Охріменко, П. Г.; Чирченко, Д. В.; Васямович, О. В. (Energy and Automation, 2017)
Methodical bases of construction of smart decision support organizing and processing of organic raw materials in biogas plants S. Shvorov, D. Komarchuk, P. Okhrimenko, D. Chirchenko, O. Vasyamovich Аnnotation. We consider the approach and methodological basis for creating hybrid of intellectual decision support system, by which ensured the formation of reasonable proposals for the organization the collection and recycling of organic materials in biogas plants (complexes). With the proposed system solve the following tasks: monitoring of energy crops and the detection of residues of organic material after harvest through the use of drones, study proposals for the use of harvesting and transport technology for the collection and recycling of organic materials in biogas complexes. Key words: intelligent decision support system, technological process, biogas facilities, organic raw materials